2020
DOI: 10.1038/s41598-020-70369-4
|View full text |Cite
|
Sign up to set email alerts
|

Insights on small molecule binding to the Hv1 proton channel from free energy calculations with molecular dynamics simulations

Abstract: Hv1 is a voltage-gated proton channel whose main function is to facilitate extrusion of protons from the cell. The development of effective channel blockers for Hv1 can lead to new therapeutics for the treatment of maladies related to Hv1 dysfunction. Although the mechanism of proton permeation in Hv1 remains to be elucidated, a series of small molecules have been discovered to inhibit Hv1. Here, we computed relative binding free energies of a prototypical Hv1 blocker on a model of human Hv1 in an open state. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 80 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…We observed the upward displacement of the S4 helix to have a strong positive net charge in channel activation, and this is consistent with previous studies [ 14 , 15 , 16 , 17 , 18 , 20 ]. Along with the upward movement of the S4 helix, a change in the hydrogen bond network ( Figure 5 ) was observed, which is consistent with previous studies [ 14 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed the upward displacement of the S4 helix to have a strong positive net charge in channel activation, and this is consistent with previous studies [ 14 , 15 , 16 , 17 , 18 , 20 ]. Along with the upward movement of the S4 helix, a change in the hydrogen bond network ( Figure 5 ) was observed, which is consistent with previous studies [ 14 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…In all of the previous studies, the homology modeling of Hv1 was built based on the structures of Kv, Nav, and the Kv1.2–Kv2.1 paddle chimera as templates, with sequence identities of less than 30% [ 13 , 14 , 15 ]. Recently, voltage-dependent structural models and the inhibitor (2GBI) binding of the human Hv1 channel were reported using the homology modeling of Hv1 based on the mHv1cc crystal structure to run molecular dynamics (MD) simulations [ 16 , 17 , 18 ]. Despite the previous research attempts, the understanding of the gating mechanisms of Hv1 is still in debate, especially with the gating mechanism under the membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…We verified that the new inhibitor core structure is compatible with the 2GBI binding site ( Hong et al, 2014 ) by docking HIF within the structural model of the Hv1 VSD in the up state that was previously used for the characterization of 2GBI binding ( Geragotelis et al, 2020 ; Lim et al, 2020 ). We set the initial position of HIF so that its 2-aminoimidazole ring and the two carbon atoms at positions 4 and 5 would overlap with the corresponding moiety of bound 2GBI.…”
Section: Resultsmentioning
confidence: 70%
“…2GBI has been shown to inhibit Hv1 through an open-channel block mechanism ( Hong et al, 2013 ). Besides F150, other residues were found to interact with the ligand, including D112, S181, and R211 from the S1, S3, and S4 helices, respectively ( Chamberlin et al, 2014 ; Gianti et al, 2016 ; Hong et al, 2014 ; Lim et al, 2020 ). To develop high-affinity inhibitors based on the HIF scaffold, it is important to establish whether the same residues involved in 2GBI binding interact with HIF or whether there are different/additional molecular determinants.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Similarly, there are studies that have shown that the Rocklin correction has very little effect on the RBFE calculations. 48 This is likely best explained by the fact that the Rocklin correction mainly corrects for the long-range effects of the electrostatic interactions. The ΔΔ G DSC ( L ), which is usually the largest component in Rocklin correction, depends on the proportion of the box that is filled with water.…”
Section: Discussionmentioning
confidence: 99%